Cytogenetic and Molecular Characterization of Sphaerophoria rueppellii (Diptera, Syrphidae) - Pedro Lorite; José M. Rico-Porras; Teresa Palomeque; Mª Ángeles Marcos-García; Diogo C. Cabral-de-Mello; Pablo Mora (Insects)
Sphaerophoria rueppellii is a Palearctic hoverfly widely used as a native biocontrol agent against aphid pests in Mediterranean agroecosystems. In this study, we present a cytogenetic analysis and characterization of the mitochondrial genome of this species. Chromosomal preparations, obtained from third-instar larvae, were used for conventional staining, DAPI staining and C-banding techniques, and major ribosomal DNA (rDNA) location by fluorescence in situ hybridization (FISH). Karyotype analysis revealed a diploid number of 2n = 10, with heterochromatic blocks in the pericentromeric regions of all autosomes and rDNA clusters on both sex chromosomes. The complete mitochondrial genome (16,605 bp) was sequenced and annotated using next-generation sequencing and assembly pipelines. It contains the typical 37 mitochondrial genes and a highly A + T-rich control region with tandem repeats. Gene order and codon usage were conserved compared with other Syrphidae. Phylogenetic reconstruction based on mitochondrial protein-coding genes clarifies the species’ placement within the Syrphini tribe. Our results contribute valuable genomic and cytogenetic information that supports comparative analyses and may aid in taxonomic clarification within the genus. These findings also offer key data that could guide the genetic optimization of S. rueppellii as an efficient, environmentally safe biological control agent in sustainable agriculture.